Remarkable enhancement of La(1-x)SmxCrO3 nanoperovskite properties: An influence of its doping concentrations. (November 2017) - Sivaprakash, P.; Ananth, A. Nitthin; Nagarajan, V.; Jose, Sujin P.; Arumugam, S.
Graphical abstract: Highlights: LSCO solid solutions have been synthesized using ball milling method for first time. Highly polycrystalline single phase LSCO with tolerance factor 0.8 < T > 0.9. Effective occupancy of dopants onto the respective lattice site is analyzed. Exhibits dendritic morphology and aggregates with decreasing dopant concentrations. Synthesized LSCO nanoperovskites exhibit room temperature antiferromagnetism. Abstract: Rare earth orthochromites of type La(1-x) Smx CrO3 ((LSCO) x = 0, 0.1, 0.3, 0.5) have been synthesized through solid state reaction. These polycrystalline samples exhibit orthorhombic crystal structure and its corresponding distortion depends on the dopant concentrations. With increasing dopant stoichiometry, the A-O bond length changes resulting in the augmentation of perovskite's physical properties. The occupancy of relatively less ionic radii dopant influences the decrease in crystallite size, blue shift in emission spectrum and intensification of the phonon characteristic vibrations. The finer particles aggregate to form dendritic morphology and become distinct on Sm/La ratio increments as identified from electron micrographs and atomic force microscopy. Ambient temperature magnetization analysis reveals the enhancement of antiferromagnetic nature upon dopant increments.